2021
DOI: 10.1155/2021/5557784
|View full text |Cite
|
Sign up to set email alerts
|

Fake Detect: A Deep Learning Ensemble Model for Fake News Detection

Abstract: Pervasive usage and the development of social media networks have provided the platform for the fake news to spread fast among people. Fake news often misleads people and creates wrong society perceptions. The spread of low-quality news in social media has negatively affected individuals and society. In this study, we proposed an ensemble-based deep learning model to classify news as fake or real using LIAR dataset. Due to the nature of the dataset attributes, two deep learning models were used. For the textua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…Less stiff models are particularly suitable when the transit of fake news is slower and its survival time in the exposed population is higher. The employed model is the standard SIR system of differential Equation (1), but certainly more complex deterministic and stochastic models may be used in order to describe the diffusion of fake news as an epidemic phenomenon as, for instance, in [50][51][52][53][54][55][56][57][58]. Moreover, it would be worth investigating how to detect fake news through sentiment analysis of tweets as suggested by [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Less stiff models are particularly suitable when the transit of fake news is slower and its survival time in the exposed population is higher. The employed model is the standard SIR system of differential Equation (1), but certainly more complex deterministic and stochastic models may be used in order to describe the diffusion of fake news as an epidemic phenomenon as, for instance, in [50][51][52][53][54][55][56][57][58]. Moreover, it would be worth investigating how to detect fake news through sentiment analysis of tweets as suggested by [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…They also obtained that TGNF performs better than its variants without the GCL module, and the TDN+TGNF module performs better than GCL+TDN on three datasets. In the paper [11], the researchers presented a Bi-LSTM-GRU-dense deep learning model based on a set of classifiers to classify news as fake or real using LIAR dataset. After experimentations, the results showed that the proposed model achieved an accuracy of 0.898, a recall of 0.916, a precision of 0.913 and an F-score of 0.914, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…In another work, Aslam et al used LIAR dataset to classify news as real or fake by using an ensemble-based deep learning model. They achieved 91.4% F1-Score from their experiments (Aslam et al, 2021). LekshmiAmmal and Madasamy obtained 88.13% F1-Score by using RoBERTa to predict fake news (Lekshmiammal & Madasamy, 2021).…”
Section: Introductionmentioning
confidence: 99%